IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN BAHASA ARAB - Sepriyadi; Rudi, Anwar (Institut Kariman Wirayudha Sumenep, 2024)
This study aims to find out how the implementation of the independent curriculum in learning Arabic class X MAN 1 Mojokerto, especially class X MAPK MAN 1 Mojokerto and the supporting and inhibiting factors of the implementation of the independent curriculum itself, the type of research is qualitative using descriptive methods, Data collection tools in this study use observation, interviews, and documentation, Data analysis is carried out using Data Reduction, Presenting Data and Drawing a Conclusion. The results of this study are: (1) the implementation of the independent curriculum in learning Arabic class X MAN 1 Mojokerto, especially class X MAPK MAN 1 Mojokerto consists of planning, implementation and evaluation. In planning, teachers prepare RPP 1 sheet in accordance with the independent curriculum, in the implementation process, using a scientific approach (Scintific Approach), while the Arabic learning process includes three domains, namely attitudes, knowledge, and skills. In the assessment evaluation process, teachers have used authentic assessments. (2) supporting and inhibiting factors for the implementation of the independent curriculum in learning Arabic class X MAN 1 Mojokerto, especially class X MAPK MAN 1 Mojokerto there are two supporting and inhibiting factors: first, factors from teachers and second, factors from students. Research suggestions are addressed to Arabic teachers of class X MAPK MAN 1 Mojokerto and Madrasah MAN 1 Mojokerto. Keywords: Implementation of the Independent Curriculum, Class X Arabic Language Learning